KONDISI OPTIMUM FUSI PROTOPLAS ANTARA JAMUR TIRAM PUTIH {Peurotus floridae) DAN JAMUR TIRAM COKLAT {Pleurotus cystidiosusy - Ira N Djajanegara; Korri El-khobar (BERITA BIOLOGI, 2009)
Genetic crossing of white oyster mushroom to introduce longer storage life trait can only be done within individuals in this particular species. However, longer storage life trait is possessed by brown oyster mushroom (Pleurotus cystidiosus) which is other species within this genus. Thefeore, protoplast fusion between white oyster mushroom (Peurotus floridae) and brown oyster mushroom (Pleurotus cystidiosus) was conducted to hopefully obtain an oyster mushroom strain that has higher production and longer storage life. Protoplast fusion was done by isolating protoplast from 5-days old monokaryotic mycelia grown in PDB. As much as 3.15 x 10 protoplasts/ml were harvested using mixture of cellulase Onozuka R-10 (1%) and macerozyme R-10 (1%) from brown oyster mushroom with 80.61% viability. Similarly, 3.71 x 10 protoplasts/ml were harvested using lysing enzyme (2%)from brown oyster mushroom with 83.68% viability. Protoplast fusion were conducted using 0% (control), 30%, 40% and 50% of PEG6000. Fusion periods were done at 10, 20 and 30 minutes. The candidate fusants were then screened using MRM (minimum regeneration media) media. Based on this experiment, the optimum conditions for protoplast fusion is 10 minutes incubation using 40% PEG6000 that yielded 121 colonies grown on MRM media as candidate fusants.